Step-by-step explanation:
the right equation is :
y-y1=m(x-x1)
y+3=3(x+4)
y+3= 3x+12
y=3x+12-3
y=3x+9
To find midpoint, we find the average or median of the two x terms and the average of the two y terms to find the right coordinate point. In this case, the average of -2 and 6 is 2, and the mean of 4 and -4 is 0, so the new coordinate point is (2,0).
Let's turn this sentence into an equation:
8n = -n + 36
Then solve:
9n = 36 => n=4
Step-by-step explanation:
g*f(x)=g(x+4)=(x+4)³
g*f(-3)=(-3+4)³
= 1³=1
Answer:
The height of the another cylinder 'h' = 7
Step-by-step explanation:
<u>Explanation</u>:-
<u>Step 1:-</u>
Surface area of the cylinder = 2пrh + 2пr^2
Given radius of first cylinder is 20cm
given height of the first cylinder is 2 cm
The surface area of first cylinder is = 2пrh + 2пr^2
= 2п(20)(2)+2п(2)^2
= 4п(20+2)
The surface area of first cylinder is 88п
<u>Step 2</u>:
given data The surface area of first cylinder is 88п is same as second cylinder also
<u>Find the height of the second cylinder</u>
Given Radius of the second cylinder r = 4
Surface area of the cylinder = 2пrh + 2пr^2 = 88п
2п(4)h+2п(4)^2 =88п
on simplification we get
2п (4h+16) = 88п
after cancellation '2п' value and on simplification, we get
4h+16 = 44
4h = 44-16
4h = 28
h=7
Therefore the height of the another cylinder is 'h' =7